PENGUJIAN KARAKTERISTIK UNJUK KERJA TURBIN MIKROHIDRO DI DESA CIASMARA - P., Bambang Teguh; Trisno, M. D.; Petot, Joni (MESIN, 2007)
Experimental study of performance characteristic of micro-hydro water turbine hasbeen done in Kabitpaten Bogor. In this study performance is defined as a turbine efficiency which isrepresented by ratio between mechanical energy provided by turbine and an available potential energyofwater at a various conditions offlow. The study was limited only at several variation ofwater flowrate because the turbine installation is only equipped by conventional control system. Water level inthe basin was measured by level water meter with the precision is around 10%, while water flow ratewas measured by bridge flow meter. Mechanical energy is calculatedfrom measurement ofrotationalmoment and rotation of shaft. The moment was measured by calibrated hydraulic dynamometer andthe shaft rotation was measured by stroboscope. Based on the test results, at the full capacity (0.305mlIs flow rate and 3.17 mhead) the turbine showed agood performance with the efficiency is around59%.